STRATEGY OF EARLY CHILDHOOD LEARNING MODEL DEVELOPMENT - Khairiah, Khairiah (UIN Fatmawati Sukarno Bengkulu, 2018)
This paper will discuss about the strategy of developing early childhood learning model. This discourse is very important to be studied in view of the development of dynamic times and curricula. Recent discoveries in the field of education require educators to innovate in producing superior educational products including early childhood education. To achieve the goal of science learning in early childhood optimally, the PAUD organizers should consider the model, approach and strategy that will be applied. And improve the process skills that must be owned by early childhood. In order to learn science is not considered as difficult and boring by early childhood.Keywords : Strategy, Early Childhood, Development